Rancangan Program Layanan Bimbingan dan Konseling untuk Mengatasi Kesulitan Belajar pada Peserta Didik Kelas IX SMPN 4 Lubuk Sikaping - Zulnia Putri; Wira Solina; Yasrial Chandra (Journal on Education, 2023)
This research is motivated by a problem, namely students do not do homework or assignments, are less active in learning in class, do not understand learning material. The purpose of this research is to describe: 1) Learning difficulties of students. 2) Guidance and Counseling Service Program Design to Overcome Learning Difficulties in Class IX Students of SMPN 4 Lubuk Attitude. This research was conducted using a quantitative descriptive method. The study population consisted of 111 students selected by proportional random sampling technique with 53 participants. The instrument used is a questionnaire. As for data analysis using interval scores and percentages. Based on the results of research on the Design of Guidance and Counseling Service Programs to Overcome Learning Difficulties in Class IX Students of SMPN 4 Lubuk Attitude: 1) Shows the results of students' learning difficulties are in the category of no learning difficulties. 2) Service program design to overcome students' learning difficulties, namely basic services with classical guidance service strategies, with the theme of learning strategies based on learning styles, using the Cooperative Learning approach. And individual planning and specialization services, with the theme of overcoming learning difficulties, with a discussion approach. The results of this study are recommended to guidance and counseling teachers so that the programs that have been packaged by researchers can be considered as input in implementing guidance and counseling programs.